DEVELOPMENT TENDENCIES OF THE RIGHT TO RECEIVE INFORMATION IN THE VIRTUAL SPACE - ILHOMBEKOV Jasurbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this scientific article, from a legal point of view, the trends in the development of the right to information in the virtual space are scientifically analyzed. The role of virtual space in the modern era of globalization is highlighted. The causes of the emergence of the Internet, the stages of its development, its role and significance today are scientifically substantiated. In the era of globalization, the importance of social networks and their place in the process of information exchange is emphasized. From the point of view of constitutional law, mass relations in the Internet sphere are analyzed by groups. As part of the study of the constitutional right of citizens to information, several functions of the virtual space are briefly touched upon through a comprehensive study of the content and nature of the Internet. The scientific article contains scientifically substantiated opinions of scientists from foreign countries about the place and role of virtual space.